Changes in HIV and syphilis prevalence among female sex workers from three serial cross-sectional surveys in Karnataka state, South India - Isac, Shajy (BMJ Open, 2015)
OBJECTIVES: This paper examined trends over time in condom use, and the prevalences of HIV and syphilis, among female sex workers (FSWs) in South India. DESIGN: Data from three rounds of cross-sectional surveys were analysed, with HIV and high-titre syphilis prevalence as outcome variables. Multivariable analysis was applied to examine changes in prevalence over time. SETTING: Five districts in Karnataka state, India. PARTICIPANTS: 7015 FSWs were interviewed over three rounds of surveys (round 1=2277; round 2=2387 and round 3=2351). Women who reported selling sex in exchange for money or gifts in the past month, and aged between 18 and 49 years, were included. INTERVENTIONS: The surveys were conducted to monitor a targeted HIV prevention programme during 2004–2012. The main interventions included peer-led community outreach, services for the treatment and prevention of sexually transmitted infections, and empowering FSWs through community mobilisation. RESULTS: HIV prevalence declined significantly from rounds 1 to 3, from 19.6% to 10.8% (adjusted OR (AOR)=0.48, p<0.001); high-titre syphilis prevalence declined from 5.9% to 2.4% (AOR=0.50, p<0.001). Reductions were observed in most substrata of FSWs, although reductions among new sex workers, and those soliciting clients using mobile phones or from home, were not statistically significant. Condom use ‘always’ with occasional clients increased from 73% to 91% (AOR=1.9, p<0.001), with repeat clients from 52% to 86% (AOR=5.0, p<0.001) and with regular partners from 12% to 30% (AOR=4.2, p<0.001). Increased condom use was associated with exposure to the programme. However, condom use with regular partners remained low. CONCLUSIONS: The prevalences of HIV infection and high-titre syphilis among FSWs have steadily declined with increased condom use. Further reductions in prevalence will require intensification of prevention efforts for new FSWs and those soliciting clients using mobile phones or from home, as well as increasing condom use in the context of regular partnerships.